Valuation of the secretarial profession in the current organizational context - Oliveira, Márcio (2021)
This research analyses the impact of tasks and competencies (personal and professional) on the valuation of the secretarial profession. The study is based on a questionnaire applied to 125 managers of Portuguese companies who perform their professional activity in a direct relationship with secretarial professionals. This research validates empirically the theoretical arguments that suggest that the importance attached to the tasks performed by secretaries has a positive impact on the valuation of the profession of secretaries, that personal and professional skills have a positive impact on the valuation of the secretarial profession and that professional skills have a positive impact on the valuation of the tasks performed by secretaries. This study reinforces the theoretical argument that points to the growing importance of the performance of these professionals and the impact that this performance brings to organisational behaviour, and the growing importance of these professionals' professional and personal competencies. The present research may serve as an indicator for leaders and managers to adjust their human resources policies and strategies, namely with regard to the promotion of strategies to promote and develop the competencies of these professionals.